THE EFFECTS OF ADDITIONAL EEL TAILED CATFISH (Paraplotosus albilabris) PROTEIN CONCENTRATE ON THE EGG TART CRUST QUALITY - Tika Anggriani; Dewita Dewita; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT  The research was carried out to determine the effect of additional eel tailed catfish (Paraplotosus albilabris) protein concentrate on the egg tart crust quality. The method used was a Completely Randomized Design (CRD) non factorial with four treatment levels, which was the additional different concentration of eel tailed catfish protein concentrate into egg tart crust: without eel tailed catfish protein concentrate (P0), 5% of eel tailed catfish protein concentrate (P1), 10% of eel tailed catfish protein concentrate (P2), 15% of tailed catfish protein concentrate (P3). The treatment was repeated 3 times, so there were 12 units of trial unit. The result of the study based on organoleptic tested, it was indicated that the additional 10 % of eel tailed catfish protein concentrate into egg tart crust (P2) was the best treatment with value of appearance 7.83, flavour 7.51, texture 7.45, and taste 8.12. Based on proximate analysis that P2 treatment was contained water, ash, protein, and fat content 3.60%, 1.51%, 8.16%, and 7.95%, respectively. Keywords: eel tailed catfish, egg tart crust, fish protein concentrate